Corporate Philanthropy and Risk Management: An Investigation of Reinsurance and Charitable Giving in Insurance Firms. Issue 1 (7th December 2016) - Adams, Mike; Hoejmose, Stefan; Kastrinaki, Zafeira
ABSTRACT: Drawing a framework from strategic stakeholder theory and using 1999 to 2010 panel data from the United Kingdom's (UK) non-life insurance industry, we examine the effect of reinsurance on the decisions to donate to charities, and the amount given. We find that reinsurance substitutes for charitable giving as it optimizes the interests of multiple stakeholders. We further note that corporate giving is directly related to the size and age of insurers, proportion of female directorships and insider ownership, but generally inhibited by chief executive officer (CEO) bonus plans, dominant shareholders, and financial experts on the board. Interestingly, when reinsurance interacts with board-level variables we find that the donations decision is positively related to CEO bonus plans, and negatively linked with inside ownership and the proportion of female board members. Our research results could have important implications for stakeholders.